Protein restriction during intrauterine and lactation periods: effects on testicular development in pre-puberty rats (Acta Scientiarum. Biological Sciences, 2015)
Current study investigates the effects of maternal protein restriction during pregnancy and lactation on the testis of immature rats. Female Wistar rats were mated and, after confirming pregnancy, they were divided into two groups: undernourished group (UG) fed on a diet with casein 8%, and control group (CG) fed on a diet with casein 17 %, during pregnancy and lactation. After weaning, male offspring from the two experimental groups were fed on normal diet up to 35 days old when they were euthanized. Body and testicular weights decreased in UG when compared to those in CG. Volumetric density of seminiferous tubules was higher in CG whilst intertubular space increased in UG. The number of lumenated seminiferous tubules was higher in CG than in UG. Tubular diameter, seminiferous epithelium height and total length of seminiferous tubules were lower in UG. Round spermatids were frequently found in seminiferous tubules cross-section of CG. On the other hand, spermatocytes I in prophases was the germ cell commonly found in seminiferous tubules cross-sections of UG. Undernutrition during pregnancy and lactation period of the male Wistar rats altered the morphometric testicular parameters related to tubular compartment and delayed the onset of spermatogenesis.